Reliability and long-term evaluation of GO-MnO2 nano material as a newer corrosion monitoring sensor for reinforced concrete structures. (July 2019) - Karthick, Subbiah; Muralidharan, Srinivasan; Lee, Han-Seung; Kwon, Seung-Jun; Saraswathy, Velu
Abstract: Graphene oxide-manganese oxide (GO-MnO2 ) nanomaterial was tried as electrochemical corrosion potential sensor and corrosion rate monitoring sensor in reinforced concrete structures. Graphene oxide-manganese dioxide nanomaterial was prepared by a simple chemical method. The synthesized material was characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), Raman spectra and transmission electron microscopy (TEM). An embeddable corrosion potential sensor (ECPS) and embeddable corrosion rate monitoring sensor (ECRMS) was assembled using nanomaterial suitable for measuring rebar potential and corrosion rate of rebar in concrete structures. The reversibility and reliability of the sensors were monitored under simulated concrete environmental conditions. The long-term stability was monitored for a period of 24 months under an active and passive state of reinforcing steel in concrete with respect to ECRMS and the results were compared with the surface mounting techniques. The stability of GO-MnO2 based ECPS and ECRMS was found to be excellent in an active and passive condition and hence can be put forth as a promising new candidate material for corrosion monitoring in concrete structures.